2007
DOI: 10.1038/sj.npp.1301432
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Preference Influences the Subthalamic Nucleus Control on Motivation for Alcohol in Rats

Abstract: In addition to its role in motor and attentional processes, the subthalamic nucleus (STN) has also been recently demonstrated to be involved in motivational function. Indeed, bilateral STN lesions modulate differentially the motivation for natural rewards and drugs of abuse, increasing motivation for food and decreasing motivation for cocaine in rats. Here, we show that in outbred rats, the STN can modulate the motivation for alcohol according to alcohol preference, without affecting alcohol intake. When perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 57 publications
2
42
2
Order By: Relevance
“…In contrast to these results, we found the opposite effects when the reward was cocaine, highlighting a possible role for STN to modulate the reactivity of the reward system with regard to the nature of the reward involved [62]. In a recent study testing the effects of STN lesions on motivation for alcohol, we have further shown that STN lesions could also affect motivation in an opposite manner depending on the initial preference of the animals for the reward [63]. Although there are no data available of STN manipulation on motivation in animal models of PD, these results are in line with some clinical observations in PD patients after STN DBS reporting craving for sweet food in some cases or decreased addictive behavior toward dopaminergic treatment [65].…”
Section: Motivational Behavior and Psychiatric Modelscontrasting
confidence: 82%
See 2 more Smart Citations
“…In contrast to these results, we found the opposite effects when the reward was cocaine, highlighting a possible role for STN to modulate the reactivity of the reward system with regard to the nature of the reward involved [62]. In a recent study testing the effects of STN lesions on motivation for alcohol, we have further shown that STN lesions could also affect motivation in an opposite manner depending on the initial preference of the animals for the reward [63]. Although there are no data available of STN manipulation on motivation in animal models of PD, these results are in line with some clinical observations in PD patients after STN DBS reporting craving for sweet food in some cases or decreased addictive behavior toward dopaminergic treatment [65].…”
Section: Motivational Behavior and Psychiatric Modelscontrasting
confidence: 82%
“…We have shown that whatever the internal state of the animals (deprived or sated) or the reward (standard animal food, palatable food, alcohol or i.v. injection of cocaine), STN lesions do not affect the consummatory processes [61][62][63] (Fig. 22.9).…”
Section: Motivational Behavior and Psychiatric Modelsmentioning
confidence: 85%
See 1 more Smart Citation
“…1C), but significantly increased the number of lever presses during the inactive period immediately following an injection (i.e., perseverative lever presses) [F (1,18) = 0.04 (ns) and 5.75, P < 0.05 for infusions and perseverative lever presses, respectively]. Consistent with the effects of bilateral STN lesions on motivation for food, cocaine, or alcohol (11,17,18), STN DBS did not affect the consummatory processes for either food or cocaine when the behavioral cost to obtain the reward is low.…”
Section: Resultsmentioning
confidence: 99%
“…The permanent elimination of FosB gene products does not alter alcohol intake but enhances the preference for sweet solution in mice (Korkosz et al 2004). Several experimental procedures, such as a lesion of the subthalamic nucleus, have been shown to increase motivation for alcohol in a self-administration paradigm without impacting alcohol intake (Lardeux and Baunez 2008). In this context, it would be important to examine the motivation for alcohol in an operant paradigm (using a progressive ratio schedule) in PRS animals (Campbell et al 2009).…”
Section: Discussionmentioning
confidence: 99%